Éléments pour une évaluation diagnostique des bas niveaux en littératie - Marc Weisser; Nathalie Gavens (Université de Provence, 2012)
Designing a teaching system adapted to the requirements of learners involves a precise knowledge of the failing processes. This text proposes a study about diagnostic evaluation of basic competences in reading. Concerned adults show difficulties with written language. Within the theoretical framework of cognitive psychology, we measured and compared with expert readers, three competences leading to the identification of written words. The results indicate that they use the indirect way preferentially. That leads us to think that the systematic teaching of elementary competences has its entire place in teaching systems.